Benessere organizzativo e rischi psicosociali in un campione di amministrazioni pubbliche italiane / Organizational wellbeing and psychosocial risk factors in a sample of Italian Public Administration work environments - Fida, R.; Gualandri, M.; Avallone, F. (La Medicina del Lavoro, 2011)
Summary«Organizational wellbeing and psychosocial risk factors in a sample of Italian Public Administration work environments». Background: It has been recognized both by the scientific community and within the framework of social policies in Europe that the physical and psychosocial working environments pose potential risks for workers and organizational wellbeing. In particular psychosocial risks concern aspects of the design and management of work and its social and organizational contexts which have the potential for causing psychological or physical problems. Objectives: This article examines the psychosocial risk factors of several types of Italian Public Administration offices (municipal, provincial, regional, central government, university, police headquarters, chamber of commerce, etc.) with the aim of obtaining a picture of the most problematic risk factors for each type. Methods: the participants of this survey consisted of about 23,500 employees of different types of Public Administration offices. The Multidimensional Organizational Health Questionnaire (MOHQ, 3) was used to collect the data. Results and Conclusions: Results from ANOVA indicated that perceptions of fairness and job demands were the most problematic risk factors. Perception of safety at work was another problematic risk factor in specific types of work. The results revealed a high perception of stress in all workers over the entire range of the public administration offices studied.